Assessing the Contribution of the Operation Wealth Creation Operation (PWC) Program to Household Poverty Reduction: A Case Study of Nyakabande Sub-county, Kisoro District - Phionah Tuyizere (Uganda Christian University, 2025)
This study assesses the contribution of the Operation Wealth Creation (OWC) program to household poverty reduction in Uganda. Initiated in 2013, the OWC program was established to enhance agricultural productivity, create employment, and improve household incomes through the distribution of agricultural inputs and advisory services. The research explores the extent to which OWC interventions have contributed to improving livelihoods and reducing poverty among rural households. A mixed-methods approach was employed, combining quantitative data collected from beneficiary households with qualitative insights from key informant interviews and focus group discussions. The findings indicate that while the program has led to increased access to agricultural inputs and some improvements in crop yields, challenges such as delayed input delivery, limited follow-up support, and lack of market access have hindered its full potential. The study concludes that although the OWC program has made notable strides in poverty alleviation, its impact can be significantly enhanced through better coordination, capacity building, and integration with broader rural development strategies. Recommendations are offered to improve program efficiency and sustainability for long-term poverty reduction
Undergraduate Research